Clinical Profile of Paraquat Poisoning from a Tertiary Care Hospital in Southern India: A Case Series - CH Karthik Reddy; Mahasweta Choudhury; Athul Suresh Rohith Atteparambil (Journal of Clinical and Diagnostic Research, 2025)
Paraquat is a 1,1´-dimethyl-4,4´-bipyridinium dichloride herbicide widely used in agriculture. It is highly toxic even in a very minimal amount (10-20 mL), which on consumption, is associated with multiorgan failure. Intoxication may be accidental or suicidal, and the route of exposure is oral ingestion, inhalation, or transdermal absorption. Few countries have banned this compound or its use is restricted, but in developing countries like India, its unrestricted availability makes it a popular tool for deliberate self-harm. This case series pertains to an observation of 15 patients admitted to a teaching hospital with paraquat poisoning. The present case series included 15 patients, mostly males 10 (66.6%) in the age group of 18-50 years. Among 15 patients, 12 were suicidal (80%), and gastrointestinal symptoms like vomiting (100%) and difficulty swallowing (66.6%) were the most common initial presentation after intake. Renal involvement was the most common (93.3%), followed by lung (60%) and liver (60%). Patients were treated with corticosteroids, cyclophosphamide, antacids, vitamin C and chlorhexidine mouthwash. Out of total patients, 8 (53.3%) underwent haemodialysis due to acute renal failure and 10(66.6%) patients received N-Acetylcysteine due to acute liver injury. Mortality of patients with paraquat poisoning was 45.45%. Paraquat poisoning is lethal with no effective antidote. Severity of the poisoning depends on amount of compound ingested. Morbidity and mortality are high due to multiorgan failure or respiratory failure due to pulmonary fibrosis. Policymakers should focus on either banning the compound or restricting its availability due to its high toxicity